Gymnasium Equipment GIF Motion Learning and Fitness Training Guide Mobile Application / Muhamad Adib Surani - Surani, Muhamad Adib (2017)
Gymnasium Equipment GIF Motion Learning and Fitness Training Guide Mobile Application or called as GYMEDU is a mobile application that created to help people learn on how to do exercises using gymnasium equipment and how to do fitness training session effectively. Nowadays, most fitness consumers who just at the beginning level to venture into active physical lifestyle do not know the basic learning on how to handle equipment and utilize them in recommended safety and effective approach. Most people also have lack of knowledge on how to carry out fitness training session combining suitable set of exercises for themselves. This mobile application is developed to help them learn both features in easier way, implementing Gagne model as proper as well as effective guideline to help them achieve personal target physical fitness performance enhancement by using this mobile application. Objectives of this project is to design and develop mobile application teaching gymnasium equipment using GIF motion and fitness training guide with both implementing four of Gagne Events of Instructional Design Model. Another objective is to carry out usability test of the mobile application. This mobile application natively developed for Android Operating System based smartphones only and implementing Analysis, Design, Development, Implementation, Evaluation (ADDIE) as research methodology framework. Usability test had been carried out to ten applicants and results have been recorded and analyzed. Overall, this project had shown strengths and some limitations with discussed recommendation of future works as well.